MODEL PENDIDIKAN KEWIRAUSAHAAN DI PERGURUAN TINGGI DALAM MENUMBUHKAN ENTREPRENEUR MUDA KREATIF DAN INOVATIF DI KOTA SEMARANG - Susanti, Martien Herna (Forum Ilmu Sosial, 2014)
Thought tobring entrepreneurship education in colleges, both of which are integrated in the curriculum and student activities were developed by several universities and is targeted by 2014as many as20 percent of college graduates managed to become a businessman (Institutions of Higher Education,December 22, 2009). The creation of community among faculty and entrepreneurs from college graduatesis intended to accelerate the addition of Indonesian business man who needed to drive economic growth in the nation. Associated with improving the quality and relevance of education which basically includes the development of the moral aspects, morals, mind, character, knowledge, skills, health, art and culture, the development of these aspects, leads to improvement and development of life skills, which is realized through the achievement of basic competencies to survive, and able to adapt them selves to succeed in life. But in fact the institution has not bee nable to resolve the problem of unemployment and bridging the world of education and business world.